Propriedades Estruturais e Espectroscópicas de Óxidos Mistos Argila/Hidróxido de Cobalto Tratados Termicamente - Barabach, Mauricio (2008)
Clays are essentially moisturized hydrated aluminum silicates, usually crystalline, that could contain iron and magnesium. They could contain others minerals, organic matter and soluble salts yet. In the physicochemical point of view, the clays can be considered as dispersed systems of minerals, in which particles with diameter below 2?m predominate. The clays are used in a series of finished products, because of possessing appropriate properties, for the abundance and for being of easy handling. They can be used as molecular sieves, as stabilizer emulsion, in the decanting, in cosmetics and tints, in nanocomposites, as decolorizing and clarifying agent of vegetable and minerals oils, as catalytic supports, as filtration agent, as absorbent of oils in water, as absorbent of heavy metals, etc. In this work we promoted the Brasgel and Verde-Lodo bentonite clays modification, that coming from the country district of Boa Vista in the state of Paraíba, through sol-gel chemistry, through the addition of a cobalt gel. The natural and modified clays were submitted to heat treatments until 1000 oC. The clays and the resultant mixed materials were submitted to structural (X-ray diffraction), thermal (thermogravimetry and differential thermal analysis), spectroscopic (infrared spectroscopy), microstructural (scanning electron microscopy) and chemical composition (energy-dispersive X-ray spectroscopy) analyses. Through these analyses, we could conclude that these clays can be used for the explicabilities purposes since heat treated up to 600 oC. This because for heat treatments above this temperature, the bentonite structure is collapsed and the clay becomes others minerals. Therefore, the modified and heat treated clays, up to 600 oC, are excellent candidates to applications as acid catalysts, electrochemical devices, electrocatalysis, sensor, among others.